Artscience: a path to transdisciplinarity (Research, Society and Development, 2023)
This study consists of a theoretical production that proposes the articulation of some ideas and references in order to create a possibility for transdisciplinarity. To do so, it seeks definitions on transdisciplinarity in the literature dedicated to this theme and builds bridges of possibility in articulation with the Artscience theoretical framework. The objective is to propose a artscience pedagogy that departs from the context of the school discipline science towards the transposition of the barriers that limit the disciplinary space. To do so, it relies on the methodological framework of the Arts-Based Educational Research (ABER). With this articulation it is possible to apprehend that the artscience perspective proposes the dismantling of apparent dichotomies created historically in the production of knowledge, such as science and art itself, objectivity and subjectivity, as well as reason and sensibility. Furthermore, together with art, especially the performing arts, it invites us to think about the multidetermination of the body in the teaching and learning process based on Somatic Education, which consists of a transdisciplinary perspective on the body that learns. Finally, it envisions in the greater awareness and criticality achieved by a artscience pedagogy, a path for social mobilization and generation of a political will to transform the lived reality.